Revisiting finance-led growth: Evidence from disaggregated bank credit in Indonesia (period 2009–2023) - Huda, Syamsul; Yuliati, Anik; Setyawan, Dendy (Journal of Economics and Business Letters, 2025)
Indonesia’s economic performance has long been intertwined with the flow of bank credit; however, the rapid expansion of lending has not always moved in harmony with growth. The varied outcomes of working capital, investment, and consumer loans raise concerns about whether credit actually promotes sustainable development or, when misdirected, risks producing an imbalance.  This study aims to clarify these dynamics by analyzing the distinct effects of disaggregated bank loans on Indonesia's economic expansion from 2009 to 2023.  Taking a quantitative approach, it uses multiple linear regression to examine the individual and collective influence of each loan category, using secondary data from Bank Indonesia and the Central Statistics Agency.  The study found that working capital loans have a favorable and significant impact, emphasizing their importance in supporting daily output and short- to medium-term growth. Investment loans typically have a negative impact because of inefficiencies, delays, and intrinsic structural flaws that obstruct their primary purpose of increasing capacity.  While consumer loans help boost household demand, their impact on macroeconomic growth is small, highlighting their limitations as long-term growth drivers.  Nonetheless, the interaction of these three loan categories is critical in shaping economic results, as models show that they account for a considerable part of the growth fluctuation.  This duality emphasizes the potential of finance as both an enabler and a constraint, implying that effective oversight of investment credit, consistent working capital flows, and careful management of consumer credit are critical strategies for promoting inclusive and resilient economic growth in Indonesia.